2015
DOI: 10.1155/2015/489842
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effect ofZingiber officinaleExtract on Growth ofStreptococcus mutansandStreptococcus sanguinis

Abstract: Background and Objectives. Tooth decay is an infectious disease of microbial origin. Considering the increasing prevalence of antibiotic resistance due to their overuse and also their side effects, medicinal plants are now considered for use against bacterial infections. This study aimed to assess the effects of different concentrations of Zingiber officinale extract on proliferation of Streptococcus mutans and Streptococcus sanguinis in vitro. Materials and Methods. In this experimental study, serial dilution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 17 publications
0
16
0
4
Order By: Relevance
“…The marker compounds contained in ginger, particularly gingerol and shogaol, have been reported exhibit important antioxidant properties with remarkable anticancer, and antimutagenic effect [12], analgesic [13], inhibit melanoma [11], inhibit platelet aggregation [14], antihyperlipidemia [15], antidiabetes [16], ameliorate renal and pancreas damage [17], and so on. Certain compounds contained in (Z. officinale) demonstrate synergistic effect as auxiliary chemical agent against on C. albicans, Enterococcus faecalis, Escherichia coli, and their endotoxins [18] and also other microbes [19].…”
Section: Discussionmentioning
confidence: 99%
“…The marker compounds contained in ginger, particularly gingerol and shogaol, have been reported exhibit important antioxidant properties with remarkable anticancer, and antimutagenic effect [12], analgesic [13], inhibit melanoma [11], inhibit platelet aggregation [14], antihyperlipidemia [15], antidiabetes [16], ameliorate renal and pancreas damage [17], and so on. Certain compounds contained in (Z. officinale) demonstrate synergistic effect as auxiliary chemical agent against on C. albicans, Enterococcus faecalis, Escherichia coli, and their endotoxins [18] and also other microbes [19].…”
Section: Discussionmentioning
confidence: 99%
“…officinale Roscoe oil was prepared using the hydro distillation method (Ali et al, 2002;Jantan et al, 2003). The concentration selected for this study was based on the respective minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) established in previous studies (Azizi et al, 2015;Lopez et al, 2005;Thosar et al, 2013) and has been reported to be effective against E. faecalis (Valera et al, 2015).…”
Section: Preparation Of Experimented Irrigantsmentioning
confidence: 99%
“…47 Activity of extracts of Zingiber officinale (ginger) and Curcuma longa (curcumin) against Giardia lamblia in vitro and in vivo was studied. Faecal cyst and intestinal trophozoite counts reduction was seen and in vivo ginger was found more effective.…”
Section: International Journal Of Pharmaceutical Sciences and Researchmentioning
confidence: 99%